Salty Ice Electrolyte with Superior Ionic Conductivity Towards Low‐Temperature Aqueous Zinc Ion Hybrid Capacitors. (30th April 2021) - Sun, Yinglun; Ma, Hongyun; Zhang, Xiaqing; Liu, Bao; Liu, Lingyang; Zhang, Xu; Feng, Jianze; Zhang, Qingnuan; Ding, Yunxia; Yang, Bingjun; Qu, Liangti; Yan, Xingbin
Abstract: Aqueous electrochemical energy storage (EES) devices have attracted considerable attention due to their advantages of low cost and high safety. However, the freeze of aqueous electrolytes usually causes the dramatic loss of ionic conduction capacity, thereby seriously restricting the low‐temperature application of such EES devices. Herein, different from traditional frozen electrolytes, a Zn(ClO4 )2 salty ice with superior ionic conductivity (1.3 × 10 −3 S cm −1 even at −60 °C) is discovered. It is attributed to the unique 3D ionic transport channels inside such ice, which enables the fast transport of both Zn 2+ ions and ClO4 − ions inside the ice at low temperatures. Using this Zn(ClO4 )2 salty ice as an electrolyte, as‐built zinc ion hybrid capacitor is able to work even at −60 °C (with 74.2% of the room temperature capacity), and exhibits an ultra‐long cycle life of 70 000 cycles at low temperature. This discovery provides a new insight for constructing low‐temperature EES devices using salty ices as electrolytes. Abstract : A unique 3D network filled with a concentrated solution is formed inside the Zn(ClO4 )2 salty ice, which endows ions with fast transport capacity in ice even at an extremely low temperature of −60 °C. Using such Zn(ClO4 )2 salty ice as an electrolyte for constructing zinc ion hybrid capacitors, the resulting device achieves excellent electrochemical performance at low temperatures.